Broadening borders to build better schools: Virtual professional learning communities. Issue 2 (15th August 2019) - Carpenter, Daniel; Munshower, Paul
Abstract : Purpose: The purpose of this paper is to explore how rural teachers provided a PLC by leveraging virtual technologies to connect educators of like subject disciplines from several schools, foreign and domestic. Design/methodology/approach: A phenomenological case study-based approach was leveraged to investigate established vPLCs at schools (Creswell, 2013 ; Stake, 2010 ). Qualitative data were collected from multiple sources to obtain rural teacher perceptions on the impact vPLCs had on their practice (Creswell, 2013 ). Findings: Teacher collaborative teams build relationships comparable to teams that met face to face as part of a similar PLC and PD experience. Participant reflections in this investigation showed that rural educators favored face-to-face meetings; however, vPLCs provided similar teacher experiences to that of the face-to-face PBL model. Results indicated that educators recognized virtual collaboration just as valuable a tool for enabling PLCs than face-to-face collaborations while still offering similarities to improved teacher practice. Research limitations/implications: The research was limited to teachers in rural settings in the USA (Texas) and in the Dominican Republic. The research was limited to teacher perceptions of change, and observed changes as part of their participation in a research-based virtual PLC model. The research was limited to the school setting over an academic year. Practical implications: The findings from this study have practical implications for rural teachers and school implementation of a professional learning community model. Originality/value: The promise provided by this study is that vPLCs may provide opportunity for rural schools to provide a job-embedded professional development model (Croft et al., 2010) for otherwise isolated teachers (Barrett et al., 2015).